The Role of Oversight Bodies in Combating Corruption in Libya: A Study of the Audit Bureau - Ben Ashour, Samia Jamal; Wali, Taha Muhammad (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
This study aims to shed light on administrative and financial corruption in Libya during the period 2015–2020, and to identify the central oversight bodies in Libya, their tasks, mandates, and the role each plays in combating corruption, with a focus on the Audit Bureau as a case study. The study addresses the central question of how effective the central oversight bodies are in reducing financial and administrative corruption. It adopts a descriptive-analytical approach to explore the phenomenon of corruption in Libya, highlighting its causes and impacts, as well as the role of oversight bodies in detecting and combating it. The study reached several key findings, most notably: the weakness of the legislative, executive, and judicial frameworks for combating corruption has hindered the efforts of specialized central bodies; and the lack of clear distinctions and overlaps in the mandates of the main central oversight bodies have led to neglect of their core role, negatively impacting their effectiveness in curbing corruption. The study recommends adopting a national policy starting with the achievement of social justice, prioritizing the application of governance in public institutions, and enhancing the system of prior oversight exercised by the Libyan Audit Bureau to significantly improve its effectiveness in reducing corruption. It also calls for granting central oversight bodies the independence and sufficient authority to fulfill their role in eradicating widespread corruption, as well as revisiting existing legislation and laws that fail to deter perpetrators, such as the lenient disciplinary sanctions stipulated in the Labor Relations Law.
Keywords: Oversight; Financial Corruption; Audit Bureau; Libya